Home Experiments And Observations As A Form Of Independent Work Of Pupils In Physics - Shermetova Sayyora Turakhodjayevna; Mavlonov Shamil Sultonovich (Genius Journals, 2025)
In this article, it was noted that in the process of teaching physics, various types of independent work are used. Formation learners' ability to work independently with educational and additional literature, schoolchildren’ independent homework in physics as necessary elements of the educational process.
Keywords: Independence in cognitive activity; acquisition of skills; educational literature